Salt marsh halophyte services to metal-metalloid remediation: assessment of the processes and underlying mechanisms - Anjum, Naser A.
Salt marshes are widely distributed and most productive ecosystems in the temperate zones on the globe. These areas perform vital ecological functions and are populated mainly by halophytes—plants that are able to survive and reproduce in environments with exceptionally high salt concentrations. In salt marshes, in addition to tolerating high salt concentrations, salt marsh halophytes have to cope with damages caused by multiple anthropgenic pressures including metal and metalloid pollution. Extensive studies have been performed aiming at exploring naturally occurring endemic salt marsh halophytes with extraordinary potential for metals and metalloids remediation. However, a knowledge gap is perceptible on the basics of salt marsh halophyte adaptation/ tolerance to the joint action of damaging factors such as high concentration of salt and presence of metals–metalloids. In light of available literature, the current paper is critical in: (i) highlighting ecological significance of salt marsh halophytes and their use as bioindicators or biomonitors of metal–metalloid pollution; (ii) analyzing salt marsh halophyte significant contributions for metal- and metalloid-remediation processes; (iii) overviewing salt marsh halophytes–microbes interaction influence on metalphytoremediation processes; and (iv) cross-talking important physiological/ biochemical strategies adopted by salt marsh halophytes for salinity-, metal-, and metalloid-tolerance. Conclusively, the paper highlights important aspects so far less explored in the context of salt marsh halophyte services to metal–metalloid remediation and underlying mechanisms. The discussion will enable researchers and environmentalists to set further exhaustive studies aiming at efficient and sustainable management of rapidly mounting salt marshes metal–metalloid contamination issues.